Materialism, Body Surveillance, Body Shame, and Body Dissatisfaction: Testing a Mediational Model - Sun, Qingqing (Frontiers in Psychology, 2018)
The present study aimed to examine the mechanisms underlying the links between materialism and body dissatisfaction. 583 Chinese undergraduate women completed a questionnaire measuring materialism, self-objectification, body shame, and body dissatisfaction. Correlational analysis showed that materialism, self-objectification, and body shame were significantly positively correlated with body dissatisfaction. The results of path analyses revealed that higher materialism predicted more body dissatisfaction, albeit indirectly, via higher self-objectification and body shame.